PMASynRM system-level NVH model with eccentricity - Ciceo, Sebastian; Chauvicourt, Fabien; Martis, Johan Gyselinckand Claudia (2020 IEEE Transportation Electrification Conference & Expo (ITEC), 2020)
This paper presents a high-fidelity system-level vibration model for a permanent-magnet assisted synchronous reluctance machine that is able to capture static and dynamic eccentricity effects. The procedure of extracting finite-element data from a series of magnetostaic analyses that include rotor displacement is presented. Afterwards, the flux-linkage state variable system-level model that uses the previous data is developed. Subsequently, the vibration-synthesis method that includes the additional time and space eccentricity-induced force harmonics is discussed and vibration response of the system-level model is presented and compared to the non-eccentric case. Additionally, the effect of different eccentricity orbits on the unbalance magnetic pull force is exemplified.